Strategi Penanggulangan Overcrowded Narapidana di Rumah Tahanan Kelas 1 Surabaya - Ramadhani, Mutiara; Yasin, Devina; Tyanti, Esya; Bahar, Mutiara; Rifqi, Niswah; Wahyudi, Kalvin (IAI Nasional Laa Roiba Bogor, 2024)
The high crime rate has resulted in overcrowding in detention centers throughout Indonesia, including Surabaya Class 1 Detention Center. Overcrowded in Surabaya Class 1 Detention Center is an important problem that requires immediate handling. This study aims to analyze overcrowded control strategies in Surabaya Class 1 Detention Center. The research method used is descriptive qualitative with data collection techniques, interviews, and documentation. The research subjects consisted of the Head of the Detention Center, General Sub Section of Personnel Administration, Sub Section of Legal Aid and Prisoner Counseling: Legal Aid Services, Warden, Prisoners. The theory used is the strategy theory by Fred R. David with three indicators, namely formulation; implementation; and evaluation. The results showed that various efforts have been made by the Central Government and the Surabaya Class 1 Detention Center. However, these efforts cannot run optimally due to obstacles originating from stakeholders such as slow court decisions, high crime rates, and policies from related stakeholders. Therefore, this study recommends the need for special attention from the government in dealing with overcrowding in all detention centers in Indonesia by involving various stakeholders and considering aspects of humanity and justice for prisoners.